Dental anxiety and sense of coherence among outpatient department patients of a dental college in Chhattisgarh: A correlational study - N Naveen; Aanchal Pradhan; Sneha Singh; Payal Borkar (Wolters Kluwer Medknow Publications, 2021)
Context: The term "dental anxiety" (DA) refers to the feeling of uneasiness one undergoes during their appointment. Sense of coherence (SoC) is known to be capable of strengthening resilience and developing a subjectively positive state of health. There have been scarce studies showing the association between these two variables. Aim: The present study correlates DA and SoC among patients visiting outpatient department for the first time of a dental college in Chhattisgarh. Materials and Methods: A cross-sectional, questionnaire study was conducted among 400 participants. SoC and DA were measured using Antonovosky's Modified DA Scale and SoC Scale (SoC 13), respectively. The Chi-square test and Pearson's correlation coefficient were used. The analysis was done using the SPSS software version 16.0. Results: Out of 400 participants, the mean age was 37.5, where the number of male participants was high (male = 265 and female = 135). 44.8% of the study participants were slightly anxious. DA according to the age and gender was found to be statistically insignificant (P ≤ 0.896), (P ≤ 0.171), respectively. The overall SoC among the study population was low and a statistically significant association between SoC and age (P ≤ 0.046) was seen. A statistically significant association was found between SoC and gender (P ≤ 0.001). The results stated that SoC is inversely proportional to DA (r = −0.97). Conclusions: The present study reflects that DA and SoC have inverse correlation.